2019
DOI: 10.1002/ptr.6272
|View full text |Cite
|
Sign up to set email alerts
|

Ascophyllum nodosum and Fucus vesiculosus on glycemic status and on endothelial damage markers in dysglicemic patients

Abstract: The aim of this study was to evaluate a nutraceutical combination containing polyphenols extracted from Ascophyllum nodosum and Fucus vesiculosus and chromium picolinate on glyemic status; secondary outcomes were considered the changes on endothelial markers. We randomized 65 dysglycemic patients to placebo or the nutraceutical agent for 6 months. We evaluated fasting plasma glucose (FPG), postprandial plasma glucose (PPG), HbA1c, fasting plasma insulin, homeostatic model assessment (HOMA) index, high sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 23 publications
(27 reference statements)
6
24
0
Order By: Relevance
“…In this study, we investigated the effects of the five-week administration of the phytocomplex obtained from two brown algae, A. nodosum and F. vesiculosus, on glycemic control and liver function of HFD-treated Wistar rats. Several studies have confirmed the multiple beneficial effects of seaweed products, since their bioactive components have antidiabetic, antiobesity, and antioxidant properties [4,13,[16][17][18][19][20]. A recent study reported that ascophyllan from A. nodosum is able to induce glucagon-like peptide-1 (GLP-1) secretion from human intestinal cells, suggesting that it may represent a useful agent for controlling blood glucose in humans [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we investigated the effects of the five-week administration of the phytocomplex obtained from two brown algae, A. nodosum and F. vesiculosus, on glycemic control and liver function of HFD-treated Wistar rats. Several studies have confirmed the multiple beneficial effects of seaweed products, since their bioactive components have antidiabetic, antiobesity, and antioxidant properties [4,13,[16][17][18][19][20]. A recent study reported that ascophyllan from A. nodosum is able to induce glucagon-like peptide-1 (GLP-1) secretion from human intestinal cells, suggesting that it may represent a useful agent for controlling blood glucose in humans [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, synthetic α-glucosidase inhibitors, such as acarbose, are currently used in the treatment of T2D. Some studies have already demonstrated that specific components of F. vesiculosus and A. nodosum (phlorotannins and fucoidans) inhibit both α-amylase and α-glucosidase, thereby delaying/decreasing sugar absorption [5,[13][14][15]21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study enrolling overweight and obese patients demonstrated that a 6-month supplementation with the same commercial extract of F. vesiculosus and A. nodosum with the addition of chromium picolinate significantly reduces the waist circumference, plasma levels of glucose, and insulin and HOMA index, suggesting an improvement in the insulin sensitivity status [ 172 ]. In addition, a reduction in HbA1c, fasting plasma glucose and insulin, postprandial plasma glucose, and HOMA-IR was observed after the administration of the same nutraceutical combination for 6 months to 65 dysglycemic patients [ 171 ]. Moreover, nearly 20% of the treated patients retuned to a normal glycemic status, and none of the placebo-treated patients.…”
Section: Clinical Studies Investigating Brown Seaweeds For Ms Treamentioning
confidence: 99%
“…Scientific studies and clinical trials have shown that this compound can inhibit digestive enzymes and carbohydrate absorption in vivo 14 and has a beneficial impact on blood glucose and insulin levels following a starch-rich meal. 15,16 OMEGA-3 MONOGLYCERIDES SCF Pharma was founded in 2009 by Samuel Fortin Ph.D. to further develop omega-3 monoglycerides discovered using marine biomass bio-guided extraction and fractionation platform of the Marine Biotechnology Research Centre's (MBRC's). Omega-3 monoglycerides are a new form of omega-3 fatty acid with superior omega-3 uptake and formulation properties.…”
Section: Polyphenolic Ingredientsmentioning
confidence: 99%